1999
DOI: 10.2508/chikusan.70.471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrate Combined with Fumarate on Methanogenesis, Fermentation, and Cellulose Digestion by Mixed Ruminal Microbes in vitro

Abstract: Mixed ruminal microbes from the rumen of a goat were incubated with nitrate or nitrite in a growth medium containing starch and cellulose. The rate of nitrate reduction was 2.5-fold faster than the rate of nitrite reduction, which brought about the accumulation of nitrite.The increase in nitrate increased the peak nitrite concentration, and prolonged the time for nitrite to disappear. The addition of nitrate decreased methanogenesis partly by the consumption of electrons, but to a greater extent by the suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 15 publications
4
63
1
1
Order By: Relevance
“…The findings concerning the effect of fumarate on methane, pH, and total and individual SCFA were consistent with other studies with different concentrations (from 8 to 30 mmol L −1 ) of fumarate with varied diets in vitro Iwamoto et al 1999). However, 30 mmol L −1 fumarate had an adverse effect on the IVDMD (30% decrease) of high-concentrate diets.…”
Section: Discussionsupporting
confidence: 80%
“…The findings concerning the effect of fumarate on methane, pH, and total and individual SCFA were consistent with other studies with different concentrations (from 8 to 30 mmol L −1 ) of fumarate with varied diets in vitro Iwamoto et al 1999). However, 30 mmol L −1 fumarate had an adverse effect on the IVDMD (30% decrease) of high-concentrate diets.…”
Section: Discussionsupporting
confidence: 80%
“…The thermodynamics of the conversion of nitrate into NH 3 is more favourable than the formation of methane and can effectively replace methanogenesis in the rumen if nitrate is available. However, in the rumen nitrate is rapidly reduced into nitrite and the rate of reduction of nitrite into NH 3 is slower (Iwamoto et al, 1999). Nitrite accumulation is undesirable as it is extremely toxic to the host animal.…”
Section: Bacteria Using Alternative H 2 Sinksmentioning
confidence: 99%
“…The rate of nitrate reduction per cell-N was not affected by fumarate. We previously reported that when fumarate was added to cultures of mixed ruminal microbes, the rate of nitrate reduction increased (Iwamoto et al, 1999). At that time, we postulated that nitrate-and fumaratereducing bacteria, such as S. ruminantium, V. parvula, and W. succinogenes grew by obtaining ATP via electron transport phosphorylation coupled with fumarate reduction.…”
Section: Transcription Of Nar Genesmentioning
confidence: 99%